(Performance of Gas Turbine Cooling System (Radiator) at PLTGU XYZ against Environmental Air Temperature) - Ni Ketut Caturwati; Yusvardi Yusuf; Muhammad Ilham Al Faiz (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2020)
The heat exchanger is an important component in the gas and steam power plant (PLTGU) industry. One of the most important heat exchangers in gas turbine cooling systems is the gas turbine radiator. The gas turbine radiator functions to cool the cooling water, which circulated to various components of the gas turbine by using environmental air as the cooling medium. The purpose of this study was to determine the effect of environmental temperature on the performance of gas turbine radiators and to compare operational data in 2017 with operational data when the study conducted in 2019. Data collected for 3 days with 2-3 hour intervals. Data processing and analysis shows that the higher the ambient temperature, the higher the radiator effectiveness value. Data in 2017 shows the highest average value of effectiveness obtained at an ambient air temperature of 35 ˚C of 71,274%. Meanwhile, data in 2019 shows the highest average value of effectiveness at an ambient air temperature of 35 ˚C of 58,859%. Thus, the average effectiveness value of gas turbine radiators has decreased by 12,415% from 2017 to 2019